Pengaruh Relationship Marketing, Experiental Marketing dan Digital Payment Terhadap Customer Loyalty (Studi Pada Kopi Komunal di Kota Mataram) - Putu Ayu Chandra Utari, Ni (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to analyze the influence of Relationship Marketing, Experiential Marketing, and Digital Payment on Customer Loyalty at Kopi Komunal in Mataram City. The data collection method used a questionnaire with a sample of 100 respondents. The analysis method used multiple linear regression analysis with the Statistical Package For The Social Sciences (SPSS) tool. The research results show that Relationship Marketing has a positive and significant effect on Customer Loyalty. Second, Experiental Marketing has a positive and significant effect on Customer Loyalty. Third, Digital Payment has a positive and significant impact on Customer Loyalty. The research results can serve as a basis for developing more effective strategies to enhance Relationship Marketing, Experiential Marketing, Digital Payment, and Customer Loyalty.